PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Kristianus Ronaldo Jemani; Teguh Erawati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to examine whether profitability has an effect on firm value, profitability has an effect on capital structure, capital structure has an effect on firm value and profitability on firm value with capital structure as an intervening variable.The study took a sample of manufacturing companies listed on the Indonesia Stock Exchange. The type of data used in this study is secondary data in the form of a company’s annual financial report. During the 2014-2018 period, there were 142 manufacturing companies. The method of determining the sample used in this study is purposive sampling, which is a sampling method determined or determined by researchers in accordance with certain criteria. Manufacturing companies are 42 sample companies. Data is also analyzed using path analysis.The results of the study include (1) profitability has a significant positive effect on firm value, (2) profitability has a significant positive effect on capital structure, (3) capital structure has a significant positive effect on firm value, (4) Profitability has a significant positive effect on firm value with capital structure as an intervening variable.